What role does mindfulness play in regulating fear of COVID-19 and associated mental health? The results of a cross-sectional study - Lee, Kunhua; Lee, Yu-Xuan; Cheng, Yu-Tung (Frontiers in Psychology, 2023)
Objectives: The pandemic has greatly impacted people’s lives and mental health. Therefore, it is now especially important to help people maintain good mental health. The positive effects of mindfulness-based practices on mental health have been demonstrated previously. However, no consensus has yet been reached on the potential mechanisms of mindfulness. This study adopted the two-component model of mindfulness to explain the relationships between fear of COVID-19, and mental health. We proposed the following hypothetical model: (1) fear of COVID-19 could affect orientation to experience; (2) orientation to experience could affect mental health. directly; (3) fear of COVID-19 could mental health directly; (4) orientation to experience could be a mediator between fear of COVID-19 and mental health. Methods: We conducted an online survey in the present study. Three hundred and forty-four respondents were recruited to participate in the present study. After informed consent, they completed the questionnaires on the websites. The participants were asked to complete a questionnaire including the Beck Depression Inventory-II, Beck Anxiety Inventory, the Taiwan version of the Five Facet Mindfulness Questionnaire, and the Fear of COVID-19 Scale. Descriptive analysis and structural equation modeling were used to analyze the data and examine the goodness-of-fit indices. Results: Our results not only showed orientation to experience playing as a mediator between fear of Covid-19 and mental health; but also confirmed the roles of nonjudgment and nonreactivity in regulating emotions. Conclusions: Experimentation and longitudinal study could be applied to examine the roles of nonjudgment and nonreactivity in the future.